STUDI LITERATUR PENDEKATAN TARL DALAM PEMBELAJARAN BAHASA INDONESIA DENGAN MODEL PEMBELAJARAN PJBL DI SDN PERCOBAAN 2 KOTA MALANG - Dita Permai Sela (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
The implementation pf the TaRL (Teaching at the Right Level) approach in learning indonesian using the PjBl (Project-based learning) model at SDN Percobaan 2 malang, class V, was initiated to improve the quality of students’ understanding of Indonesia. The background to this research is the challenge in understanding basic Indonesian concepts by stufent and the need to create more dynamic and contextual learning. The research method uses is a literature review approach to analyze the relevance and effectiveness of the two approaches in the context of Indonesia language learning. The aim is to analyze the potential for synergy between TaRL and PjBL in creasingstudent understanding and disseminating challenges and obstacles in the implementation of these two approaches. The results of discussion show that integration between the TaRL approach and the PjBL model create a more dynamic and adaptive learning environment TaL ensures each student ganis a deep understanding of basic Indonesian concepts while PjBl allaws students to apply their understanding in the context of aurhentic assigments or projects. Nevertheless, implementing this second approach overcomes the challenges of managing heterogeneous classes and ensuring effective integration in the curriculum and learning schedule. In cobclusion, with the right support, the implementation of TaRL and PjBL at SDN percobaan 2 malang is expected to improve the quality of Indonesian languge learning, preparing students to face more complex material with ore confidence and competence.